A first report of decapod crustaceans (Anomura and Brachyura) from Laje de Santos: a no-take marine reserve in the southeast coast of Brazil - Isabela R. R. Moraes; Thiago M. Davanso; Alexandre R. da Silva; Valter J. Cobo; Douglas F. R. Alves; William Santana; Fernando L. Mantelatto; Antonio L. Castilho (Revista Mexicana de Biodiversidad)
This study represents an unprecedented effort to assess the diversity of rocky infralittoral decapod Brachyura and Anomura from the Laje de Santos Marine State Park, a preserved and protected area along the southeastern Brazilian coast. The samples were carried out quarterly for one year, using the combination of artificial refuge substrate for the passive capture of specimens and SCUBA dive for active capture. Specimens sampled were deposited in the Crustacean Collection of the Department of Biology of FFCLRP, University of São Paulo. The abundance and richness is expressive considering the dimension of the area with a total of 987 individuals distributed into 32 species, 22 genera, and 11 families. The hermit crab Pagurus brevidactylus and the crab Mithraculus forceps were the most abundant species of Anomura and Brachyura, respectively. This is the first study focused on carcinofauna inhabiting the park on and we encourage future works focused in the monitoring of species as well as the construction of new robust checklists contents from different offshore regions in order to build biodiversity parameters to serve as baseline for future management and work plans on Brazilian protected areas since decapod crustaceans are key group on fauna composition in any subtidal ecosystem.